2010
DOI: 10.1007/s10612-010-9117-5
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Crimes of Dow Chemical and the Failure to Regulate Environmental Pollution

Abstract: A case study of Dow Chemical Company using scholarly research, journalistic investigations, and government documents reveals the existence of the criminogenic corporate-state. The Corporate-State manages and regulates itself with limited interference from the Environmental Protection Agency and in the form of Dow Chemicals is responsible for numerous environmental crimes both nationally and globally all of which have been linked to numerous health, labor and economic problems. Future researchers are encouraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…On a cognitive level, managers, and even security personnel, are often unaware of the risk and implications of becoming victim to a cyber-incident, and of suitable preventative measures. As corporate crime literature on industrial hazards [18,29,30,44] has already demonstrated, the assumption that firms will take sufficient measures to protect not only themselves and their personnel, but also their wider environment from harm in the absence of external pressure is often problematic. This paper adds to this scholarship an analysis of the emerging risk of cybersecurity, in particularly in highly connected industries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a cognitive level, managers, and even security personnel, are often unaware of the risk and implications of becoming victim to a cyber-incident, and of suitable preventative measures. As corporate crime literature on industrial hazards [18,29,30,44] has already demonstrated, the assumption that firms will take sufficient measures to protect not only themselves and their personnel, but also their wider environment from harm in the absence of external pressure is often problematic. This paper adds to this scholarship an analysis of the emerging risk of cybersecurity, in particularly in highly connected industries.…”
Section: Resultsmentioning
confidence: 99%
“…It describes the collaborate governance structure of cybersecurity in chemical industries, the efforts of chemical firms in the port of Rotterdam to prevent industrial hazards related to cybercrime, and the role of public authorities in ensuring corporate cybersecurity. Criminological scholarship on industrial hazards, corporate environmental harm and corporate negligence has frequently demonstrated how corporations fail to invest in adequate measures to protect their personnel and environment from accidents [18,20,29,30]. This paper adds to this scholarship by studying how firms prevent industrial hazards and environmental harms caused by cybercrime.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…Both approaches involve a consideration of who is committing the crime or harm and why that person, group or entity is committing the harm or crime. With respect to the former, green criminologists have sought to identify and otherwise bring to light individual or micro‐level offending (see, e.g., Groombridge 2013), group or mezzo‐level offending (see, e.g., Brisman, ), including organized crime groups (Ruggiero & South, ; Sergi & South, ), and, most often, corporate or state or corporate‐state / state‐corporate offending (see, e.g., Katz, ; Kramer, ). Indeed, environmental crimes that are facilitated by nation‐states, as well as—or in conjunction with—corporations and other powerful actors—are particularly pernicious “in so far as these institutions have the capacity to shape official definitions of environmental crime in ways that allow or condone [or perpetuate] environmentally harmful practices” (White, :3).…”
Section: Causes Consequences and Prevalence Of Environmental Crime Amentioning
confidence: 99%
“…Both approaches involve a consideration of who is committing the crime or harm and why that person, group or entity is committing the harm or crime. With respect to the former, green criminologists have sought to identify and otherwise bring to light individual or micro-level offending (see, e.g., Groombridge 2013), group or mezzo-level offending (see, e.g., Brisman, 2014), including organized crime groups (Ruggiero & South, 2010;Sergi & South, 2016), and, most often, corporate or state or corporate-state/state-corporate offending (see, e.g., Katz, 2010;Kramer, 2013).…”
mentioning
confidence: 99%
“…This is a Habermasian expression that the authors identify with the capacity of managers to 'limit the potential for workers and their representative organisations to participate in decision-making processes which bear crucially upon the possible prevention of industrial accidents' (Pearce and Tombs 1998: 141). Classic case studies within the area of chemical crimes include the range of illegal conducts found in the pharmaceutical industry and the notorious Bhopal disaster, caused by the toxic gas leak at the Union Carbide plant in India (Braithwaite 1984;Cassels 1993;Kluin 2013;Pearce and Tombs 1993 As Katz (2010) describes, the involvement of Dow Chemical in the production of herbicides for military use provides a classic case study of state-corporate crime. It began in World War II as part of a project that was initially based at the University of Chicago but soon re-located to the military research facility at Fort Detrick, to produce a herbicide with the now obvious intention of investigating the potential of the chemical as a weapon.…”
Section: Beyond Petroleum?mentioning
confidence: 99%